Interpretative Differences between the Interpreters of the Seventh Century AH in the Second Part of Surat Al-Baqarah from Verse 142 to Verse 146 - Haraj , Samar Radam; Latif, Abdul Qader Abdul Hamid Abdul (Journal of Ecohumanism, 2024)
Objectives: To identify the approaches of the interpreters in the seventh century AH; by studying their sayings and evidence by studying their sayings and evidence, and thus it is possible to identify the value of their interpretations, and the features of each interpretation, as it is the ultimate goal that a student of knowledge cannot do without, and to collect the sayings of the interpreters of the seventh century AH in interpretation in one place, in which the difference occurred in the second part of the Holy Quran from verse 142 to verse 151. Methodology: Mentioning the definition of research terms, mentioning the reasons for the difference, and the difference between it and the disagreement, and as for what pertains to studying the interpretive differences, I mentioned the verse in which the disagreement occurred written in the Ottoman script, and writing the verse number, and if two issues were mentioned in the verse, this would be noted, with the presentation of all the sayings mentioned in the interpretation of the disputed verse from all the interpretations that I relied on in the text of this research. Results: Among the most important findings of the research; There are differences from the viewpoints of interpreters, as the reader of interpretation books finds that most of the verses of the Holy Quran can bear several interpretations that the interpreters have addressed, and showing the different benefits, in order to achieve correctness and avoid the statements that the enemies of Islam wanted to enter into the field of differences to challenge the Book of God Almighty. Conclusion: The scholars of the seventh century AH paid great attention to the Holy Quran, memorization, study, and interpretation, and God Almighty prepared to serve His precious book men who devoted themselves to serving the Book of God in all its various sciences.